2022
DOI: 10.1038/s41541-022-00568-9
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neutralizing antibodies and preserved cellular immunogenicity against SARS-CoV-2 in systemic autoimmune rheumatic diseases

Abstract: Reports on vaccine immunogenicity in patients with systemic autoimmune rheumatic diseases (SARDs) have been inconclusive. Here, we report the immunogenicity of heterologous prime-boost with an inactivated vaccine followed by an adenoviral vector vaccine in patients with SARDs using anti-RBD antibodies, neutralizing capacity against Omicron BA.2 [plaque-reduction neutralization test (PRNT)], T cell phenotypes, and effector cytokine production at 4 weeks after vaccination. SARD patients had lower median (IQR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A decline in vaccine immunogenicity has been observed in patients with ARDs receiving immunosuppressive drugs [ 5 , 6 , 7 , 8 ]. However, some studies have reported a preserved cellular response after homologous ChAdOx1/ChAdOx1 or heterologous CoronaVac/ChAdOx1 vaccines, suggesting the beneficial effect of the vaccine [ 6 , 16 ]. Moreover, because of the waning of immunogenicity over time and the emergence of the SARS-CoV-2 variants of concern (VOCs), third and fourth vaccinations with mRNA vaccines are now recommended in both healthy and vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decline in vaccine immunogenicity has been observed in patients with ARDs receiving immunosuppressive drugs [ 5 , 6 , 7 , 8 ]. However, some studies have reported a preserved cellular response after homologous ChAdOx1/ChAdOx1 or heterologous CoronaVac/ChAdOx1 vaccines, suggesting the beneficial effect of the vaccine [ 6 , 16 ]. Moreover, because of the waning of immunogenicity over time and the emergence of the SARS-CoV-2 variants of concern (VOCs), third and fourth vaccinations with mRNA vaccines are now recommended in both healthy and vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a proof-of-concept heterologous vaccine study demonstrated superior anti-RBD IgG, Nab, and T-cell reactivity after ChAdOx1-nCoV-19 vaccination boosted by the BNT162b2 vaccine, compared to homologous regimens in both healthy populations and patients with ARDs [ 29 ]. In addition, we previously reported that T-cell function was preserved, including IFN-γ + CD4 + T cells, IFN-γ + CD8 + T cells, and TNFα + CD4 + T cells, in patients with ARDs who received heterologous CoronaVac/ChAdOx1 as a primary series vaccine [ 16 ]. Mahasirimongkol et al also demonstrated the benefit of using an inactivated vaccine, followed by the ChAdOx1-nCoV-19 vaccine, compared to homologous regimens with an inactivated vaccine or to an adenoviral vector vaccine in a healthy population [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PRNT was carried out at the Institute of Biological Products at the Department of Medical Sciences. The experiment was performed as described previously [ 13 ]. In short, Vero cells were seeded and incubated at 37 °C for 1 day.…”
Section: Methodsmentioning
confidence: 99%